Employing Efficient Algorithms to Reduce the Distance Traveled in Location-Routing Problems Considering Travel and Service - Amir-Mohammad Golmohammadi; Alireza Goli; Hasan Rasay (مدیریت نوآوری و راهبردهای عملیاتی)
Purpose: The study aims to present a mathematical model for reducing system costs by adequately locating the required warehouses and routing vehicles that carry the products from the warehouses within a time window.Methodology: Concerning the specific nature of the location-routing problem, the consumption of fuel and the depreciation of vehicles are directly affected by the distance covered. The model proposed in this research seeks to minimize the undue length of the distance that vehicles have to travel. Moreover, to approximate the model to real-world conditions as much as possible, the 'time window' concept is employed to determine the maximum allowable time for the distribution of goods.Findings: Three metaheuristic algorithms, including NSGA-II, PAES, and MOICA, are used to solve the proposed model. Several problems of different sizes are introduced and solved to evaluate the efficiency of the solutions. Then, the results are compared regarding the SM, MID, and QM criteria. The comparative results suggest the superiority of the MOICA algorithm for big-size problems.Originality/Value: Setting a time window to reduce the distance travelled by the vehicles gets the model close to real-world conditions. It also makes it possible to estimate the costs more accurately.